An Investigation of the Output Characteristics of Photovoltaic Cells Using Iterative Techniques and MATLAB® 2024a Software - Hysa, Azem; Mahmoud, Mohamed Metwally; Ewais, Ahmed (Control Systems and Optimization Letters, 2025)
This study investigates the characteristics of photovoltaic (PV) cells using iterative methods and MATLAB® 2024a software. Its main objective is to analyze the power-voltage (P-V) and current-voltage (I-V) characteristics for various series resistances and solar irradiation levels. The precision and dependability of this study are improved by the software utilized for numerical simulations and analysis. Since the PV cells are nonlinear, numerical techniques are favored in this situation to solve their nonlinear equations. In order to investigate different curves and their characteristics, the study makes use of numerical simulations, the single diode model, and the Newton-Raphson method (NRM), which is iterative and converges to an optimal solution of the problem to be solved. The behavior of PV cells under the variation of solar irradiance and different values of series resistance is described by the I-V and P-V characteristics. From the data, we notice that the influence of sun irradiance on PV cells, demonstrates that higher solar irradiance gives more current and power, and higher series resistance decrease the output power. The highest efficiency of a solar cell measured is roughly 47.1%. Future technical advancements in these crucial areas for humankind will result in further increases in the maximum efficiency of solar cells.